Prospects of Plant-Based Systems as an Eco-Technological Approach for Heavy Metals Removal from Polluted-Waters - Perez, Leonardo Martin (2021)
Contamination of natural waters by the release of aqueous effluents containing organic and inorganic poisoning substances, mostly from agro-industrial origin, has been hard increased since the beginning of the 21st century. In the last decades, environmental contamination with heavy metals has turned to a worldwide problem due to the fast growing of industrialization and urbanization. Metals are major pollutants of fresh-water reservoirs because of their non-biodegradability and highpersistence in nature. In addition, some metals are highly toxic even at very low concentrations [1]. Heavy metals are not only a serious threat to the environment but also to all living beings, including humans, since all metallic ions are inert to chemical and biological degradation and can be transferred through the trophic chain [2].